2001
DOI: 10.1021/nl015640u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Contact Angles of Water Droplets in Carbon Nanotubes

Abstract: We study the behavior of water droplets confined in a carbon nanotube by means of parallel molecular dynamics simulations. We report radial density profiles, radial hydrogen bond distributions, and contact angles for tube radii ranging from 12.5 to 37.5 Å and for droplets containing up to 4632 water molecules. Our results indicate nonwetting behavior of the pristine CNT at room temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
170
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(183 citation statements)
references
References 22 publications
9
170
0
4
Order By: Relevance
“…The SPC/E water model was used to describe the liquid water as this water model has been investigated comprehensibly [31][32][33][34][35] . The parameter for nitrogen gas was the Universal Force Field (UFF) model which was used by Wang et al 19 .…”
Section: Interaction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPC/E water model was used to describe the liquid water as this water model has been investigated comprehensibly [31][32][33][34][35] . The parameter for nitrogen gas was the Universal Force Field (UFF) model which was used by Wang et al 19 .…”
Section: Interaction Modelsmentioning
confidence: 99%
“…Werder et al 34,35 . The standard Lorentz-Berthelot type mixing rules were used to obtain the LJ parameters between atoms of different species in both sets of potential parameters as shown in Table 1.…”
mentioning
confidence: 99%
“…Recent investigations have increased our understanding of confined water, showing that, in nanoscopic proportions, many water properties differ drastically from those of bulk water [10,11,12]. In particular, an excellent model is water confined in carbon nanotubes, which have been adopted in many previous studies [13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Among these interesting investigations, Koga et al investigated water inside single-walled carbon nanotubes (SWCNTs) of diameter 1.1∼1.4 nm and found that water forms ice nanotubes composed by a rolled square ice sheet [14,15,16].…”
mentioning
confidence: 99%
“…The geometrical shape of the meniscus and the position of the liquid surface were found by fitting the contour lines corresponding to = ͑1 / 2͒ bulk with circular arcs. 19 To ensure the smoothness of the contour lines, at least 5 ϫ 10 5 samples of the liquid density were taken in calculating the average, and the points within 5 Å from the wall and 2 Å from the center axis were neglected in the fitting procedure.…”
mentioning
confidence: 99%